Pengembangan Digital B-OK Bentuk Muka Bumi Malang Raya sebagai Sumber Belajar IPS SMP Kelas VII - Nadhianty, Ardhina; Purnomo, Agus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Social Studies is one of the subjects that has a variety of learning material, one of which is the natural environment. The natural environment as a learning material has several limitations so that media is needed that functions as a container in the process of conveying messages to students. The media that can be used to address these problems is digital books. This study aims to describe the prototype development design of Digital BOK with the material of the Earth Form of Malang Raya. The results of research and development are in the form of a digital book that contains material on the shape of theÂ Earth of Malang Raya in PDF format accompanied by a QR Code that can be accessed by users to view videos of the topography of Malang Raya which is expected to be able to provide alternative learning material and supplement books, as well as a form of implementing environmental digitization. around students. Product development in this study uses an RD (Research and Development) approach with ADDIE design. The results of product validation show the percentage score of 85% for validation of learning content, 80% for language validation, and 97.5% for learning media validation. Meanwhile, the results of trials on prospective users or validation by social studies teachers at SMP obtained an average percentage of 84.7%. Based on these percentages, it can be concluded that the Digital B-OK Bentuk Muka Bumi Malang Raya can be categorized as